2018
DOI: 10.1016/j.jtos.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Corneal nerve regeneration after herpes simplex keratitis: A longitudinal in vivo confocal microscopy study

Abstract: Our results demonstrate that although corneal nerve regeneration occurs in patients with HSV keratitis, this change is not clinically significant and does not results in changes of corneal sensation. Therefore, these patients need to be followed closely for complications of neurotrophic keratopathy and might benefit from neuro-regenerative therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Presumably, it may be the subsequent feedback from the nerve injury or degeneration. The morphological characteristics of corneal nerve regeneration remain to be clearly elucidated 1720. In the present study, increased nerve density, length, branching and tortuosity were observed in the EM patients, indicating an attempt of corneal subbasal nerves to regenerate.…”
Section: Discussionsupporting
confidence: 46%
“…Presumably, it may be the subsequent feedback from the nerve injury or degeneration. The morphological characteristics of corneal nerve regeneration remain to be clearly elucidated 1720. In the present study, increased nerve density, length, branching and tortuosity were observed in the EM patients, indicating an attempt of corneal subbasal nerves to regenerate.…”
Section: Discussionsupporting
confidence: 46%
“…It is well-known that herpes simplex [ 28 ], herpes zoster [ 29 ] and refractive surgery [ 30 ] can cause corneal nerve damage, which can be detected as decreased nerve density by IVCM. Post-herpetic neuralgia stems from damage to peripheral and central neurons that may be due to either inflammation and/or viral infection, and it is known as one of the most painful conditions [ 31 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chronic post-herpetic neuralgia does not develop with all acute episodes and can occur after several acute episodes. Interestingly, even long-term follow-up has shown that nerve density may not be restored to healthy levels after herpetic eye disease [ 28 , 29 ]. Similarly, persistent nerve loss over many years has been shown following refractive surgery [ 17 , 30 , 39 – 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a significant correlation between corneal nerve abnormalities (decreased corneal nerve density and nerve regeneration) and post-herpetic corneal sensation Hamrah et al, 2013;Cruzat et al, 2016;Moein et al, 2018). Post-herpetic neuralgia (PHN) is a chronic and refractory neuropathic pain that persists for 3 months or more after an outbreak of acute herpes zoster infection.…”
Section: Corneal Neuropathies Associated With Ocular Painmentioning
confidence: 99%